2023
DOI: 10.3390/s23042222
|View full text |Cite
|
Sign up to set email alerts
|

Beef Quality Classification with Reduced E-Nose Data Features According to Beef Cut Types

Abstract: Ensuring safe food supplies has recently become a serious problem all over the world. Controlling the quality, spoilage, and standing time for products with a short shelf life is a quite difficult problem. However, electronic noses can make all these controls possible. In this study, which aims to develop a different approach to the solution of this problem, electronic nose data obtained from 12 different beef cuts were classified. In the dataset, there are four classes (1: excellent, 2: good, 3: acceptable, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Many studies demonstrated the widespread use of e-nose in assessing food quality-related properties, including the detection of Salmonella (Gonçalves et al, 2023), the quality status of fruits (Buratti et al, 2018;Qiu et al, 2014Qiu et al, , 2015, the quality of oils (Hosseini et al, 2023), and the detection of contaminated foods (Feyzioglu & Taspinar, 2023;Putri et al, 2023;Tian et al, 2023Tian et al, ). et al, 2019.…”
Section: Figurementioning
confidence: 99%
“…Many studies demonstrated the widespread use of e-nose in assessing food quality-related properties, including the detection of Salmonella (Gonçalves et al, 2023), the quality status of fruits (Buratti et al, 2018;Qiu et al, 2014Qiu et al, , 2015, the quality of oils (Hosseini et al, 2023), and the detection of contaminated foods (Feyzioglu & Taspinar, 2023;Putri et al, 2023;Tian et al, 2023Tian et al, ). et al, 2019.…”
Section: Figurementioning
confidence: 99%
“…Matrixes to differentiate between the actual and expected values of the model's constituent parts in Java applications were classified into faulty and non-faulty classes using four confusion matrix measures: TP, FP, TN, and FN. The figure shows the confusion matrix of binary classification [41]- [44]. Figure 6 shows the confusion matrix of binary classification [45].…”
Section: Confusion Matrixmentioning
confidence: 99%
“…A confusion matrix created for two classes and the parameters it contains are given in Table 2. True Positive (TP); correctly classified positive samples, True Negative (TN); correctly classified negative samples, False Positive (FP); falsely classified positive samples and False Negative (FN); refers to negative samples that were incorrectly classified [28,29].…”
Section: Performance Metrics and Confusion Matrixmentioning
confidence: 99%